Peran Orang Tua Dalam Meningkatkan Motivasi Belajar Anak Sekolah Dasar - Vera Tri Astuti; Risa Trividia Utari; Dinda Arisania; Nelly Astuti (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
Learning motivation plays a crucial role as a driving force for success in the educational process, especially during the primary school years, a period of rapid cognitive and emotional development in children. Parents, as the first educators, have a significant influence in shaping children's learning motivation, which is generally provided through consistent attention, guidance, or encouragement. This study uses a descriptive method with a literature review approach to analyze the involvement of parents in enhancing children's learning motivation. The results show that active parental involvement in their children's education can increase both interest and learning outcomes. However, if parents do not fully understand their role in supporting learning motivation, the outcomes may be less optimal.